MODIFIKASI PATI BIJI ALPUKAT (Persea Americana Mill.) MENGGUNAKAN RAGI TAPE (Saccharomyces cerevisae) - I Sukma; Mohammad Fuad Fauzul Mu'tamar; Asfan Asfan (Agroindustrial Technology, University of Trunojoyo Madura, 2019)
Avocado seed has many useful substances such as starch, Avocado seeds also have a starch percentage 23%. Natural starch has a limited application because it not applicative. Because of this, modification was required to improve the function of the starch, which is by modifying the starch with fermentation. The factors that influence the material modification process are yeast concentration and fermentation duration. The purpose of this study was to determine the effect of yeast concentration and duration of fermentation on types of avocado seed starch. The study design used by Factorial Design (RALF) with two factors: yeast concentration 0%, 6%, 8% and fermentation time 24 hours, 48 hours, 72 hours. The research parameters included measuring gelatiniation time, gelatinasation temperature measurement, pH test and viscosity test. The results showed that the fermentation time with yeast concentration have a significant effect on pH of the material, gelatinization temperature, viscosity and starch granules. Based on the pH test parameters, the starch which had the lowest pH was 8% yeast measurement with 72 hours fermentation time (zc) that is 5.4.